The influence of grip on oxygen consumption and leg forces when using classical style roller skis - Ainegren, M.; Carlsson, P.; Laaksonen, M. S.; Tinnsten, M. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of this study was to investigate the influence of classical style roller skis' grip (static friction coefficients, MicroS) on cross-country skiers' oxygen consumption and leg forces during treadmill roller skiing, when using the diagonal stride and kick double poling techniques. The study used ratcheted wheel roller skis from the open market and a uniquely designed roller ski with an adjustable camber and grip function. The results showed significantly (P </= 0.05) higher oxygen consumption (~ 14%), heart rate (~ 7%), and lower propulsive forces from the legs during submaximal exercise and a shorter time to exhaustion (~ 30%) in incremental maximal tests when using roller skis with a micro S similar to on-snow skiing, while there was no difference between tests when using different pairs of roller skis with a similar, higher micro S. Thus, we concluded that oxygen consumption (skiing economy), propulsive leg forces, and performance time are highly changed for the worse when using roller skis with a lower micro S, such as for on-snow skiing with grip-waxed cross-country skis, in comparison to ratcheted wheel roller skis with several times higher micro S.